Susceptibility of N'Dama and Boran cattle to sequential challenges with tsetse-transmitted clones of Trypanosoma congolense - Paling, R.W.; Moloo, S.K.; Scott, J.R.; Gettinby, George; McOdimba, F.A.; Murray, M. (Wiley, 1991)
Summary The susceptibility of N'Dama cattle (Bos taurus) to four consecutive infections with different tsetse‐transmitted clones of Trypanosoma congolense was compared with that of Borans (Bos indicus). All animals were aged 13 months al the start of the study and had been born and raised free from trypanosomiasis under the same management and nutritional conditions, thereby limiting environmental factors that could have influenced susceptibility. While cattle of both breeds were equally susceptible to the establishment of trypanosome infections, the N'Damas exhibited superior resistance. Despite infection with virulent parasites, the N'Damas gained weight at the same rate as uninfected control animals, they did not develop anaemia to the extent that trypanocidal drug treatment was required, and all made a spontaneous recovery to normal hacmatological values within two to four months. In contrast, all the Borans needed treatment during the course of the four infections because of severe anaemia and showed markedly reduced liveweight gains. These clinical differences in the N'Damas were associated with two repcatable characteristics, namely, the ability to control parasitaemia and to‘resist’ anaemia, processes that did not appear to be linked. Also in contrast to the Borans. the N'Damas were able to mount accelerated haemopoietic responses, resulting in the reduced severity of anaemia following a primary infection. These findings pose the question as to whether the ability to control parasitaemia and to‘resist’ anaemia could be used as criteria for identifying resistant or trypanotolerant cattle.